Kontribusi Tarekat Naqsyabandiyah Dalam Pembinaan Pendidikan Akhlak Santri Dayah MUDI Mesjid Raya Samalanga - Fikar Aan Zulfahmi; Ammar Zainuddin; Mauhibur Rokhman (LP3M IAI Al Urwatul Wutsqo Jombang, 2024)
This research aims to determine the contribution of the Naqsyabandiyah congregation in fostering moral education for students at the Dayah MUDI Mesjid Raya Samalanga, Aceh. This research is field research with a case study approach. The data collection methods used were observation, interviews and documentation. The data analysis technique uses qualitative data analysis with descriptive methods. The research results show that implementing the Naqsyabandiyah order at Dayah MUDI Mesjid Raya Samalanga significantly contributes to Santri's moral development. The implementation method is carried out systematically, including registration, following a series of dhikr and riyadhah practices, and guidance from murshids and caliphs. The contributions of the Naqshbandiyah order include cleansing themselves of dishonorable morals, stemming the spread of heretical teachings, forming individuals with noble character and obedience to Allah, increasing worship and good morals, and raising awareness of Allah's supervision. The moral development of students is carried out through the methods of habituation, example, and socializing. The good implementation of the Naqshbandiyah order, supported by efforts at habituation, example, and the concept of socializing, has positively improved the morals of Dayah MUDI Mesjid Raya Samalanga students.